2012
DOI: 10.22358/jafs/66132/2012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exogenous enzymes and <i>Salix babylonica</i> extract or their combination on haematological parameters in growing lambs

Abstract: The aim of this study was to compare the use of exogenous enzyme preparations (EZ) and/or Salix babylonica extract (SB) or their combination as feed additives on some haematological parameters in growing lambs. Twenty Suffolk lambs of 6 to 8-months-old with 24±0.3 kg body weight were used in the study. Lambs were divided into 4 groups of 5 animals each in a completely randomized design and the treatments were: 1.control: fed a basal diet of concentrate (30%) and maize silage (70%); 2. EZ: fed the basal diet pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…Interleukin 8 has been related to the degranulative effects of neutrophils and its gene overexpression has been described when polyphenols are added to rations (Taub et al 1996;Jung et al 2009). Increases in plasma proteins have also been observed when adding an extract rich in phenols to lamb diets (Rivero et al 2012); and, as observed here, these changes were not related to infectious agents or chronic inflammatory processes, confirmed by the albumin and globulin values (Russell and Roussel 2007).…”
Section: Discussionsupporting
confidence: 72%
“…Interleukin 8 has been related to the degranulative effects of neutrophils and its gene overexpression has been described when polyphenols are added to rations (Taub et al 1996;Jung et al 2009). Increases in plasma proteins have also been observed when adding an extract rich in phenols to lamb diets (Rivero et al 2012); and, as observed here, these changes were not related to infectious agents or chronic inflammatory processes, confirmed by the albumin and globulin values (Russell and Roussel 2007).…”
Section: Discussionsupporting
confidence: 72%
“…These improvements were reflected in the feed conversion ratios, which improved by 25•7% for EZSB, 13•5% for EZ and 3•2% for SB treatments. The increased feed intake, nutrient digestibility and daily gain with the administration of SB extract and/or enzymes may be related to the positive effects of metabolites contained in the extract (Jiménez-Peralta et al 2011;Rivero et al 2012: Salem et al 2014a, and/or the action exerted by the enzymes (Rivero et al 2012). Researchers have demonstrated that a positive correlation between feeding animals diets supplemented with fibre-degrading enzymes, their performance and modes of action are uncertain (Alsersy et al in press).…”
Section: Discussionmentioning
confidence: 99%
“…The most important factor should be the dose of the additives administered (Jiménez-Peralta et al 2011;Salem et al 2013). Rivero et al (2012Rivero et al ( , 2013 stated positive effects on Suffolk lamb performance with no effects on blood chemistry when both SB extract and ZADO ® enzymes were administered together.…”
Section: Nitrogen Utilization and Purine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that only the combination of Salix babylonica extract and enzyme had a significant effect on meat quality parameters but no significant effects with only the enzyme addition (Cayetano et al, 2013). A study by Rivero et al (2012) reported the effect of Salix babylonica extracts and exogenous enzymes separately and as a combination on haematological parameters in growing lambs where no effect with any treatment observed. Giraldo et al (2009) Table 2).…”
Section: Sheepmentioning
confidence: 99%